Cardiac cachexia: Perspectives for prevention and treatment - Okoshi, Marina Politi [UNESP]; Capalbo, Rafael Verardino [UNESP]; Romeiro, Fernando G. [UNESP]; Okoshi, Katashi [UNESP] (Sociedade Brasileira de Cardiologia, 2017)
Cachexia is a prevalent pathological condition associated with chronic heart failure. Its occurrence predicts increased morbidity and mortality independent of important clinical variables such as age, ventricular function, or heart failure functional class. The clinical consequences of cachexia are dependent on both weight loss and systemic inflammation, which accompany cachexia development. Skeletal muscle wasting is an important component of cachexia; it often precedes cachexia development and predicts poor outcome in heart failure. Cachexia clinically affects several organs and systems. It is a multifactorial condition where underlying pathophysiological mechanisms are not completely understood making it difficult to develop specific prevention and treatment therapies. Preventive strategies have largely focused on muscle mass preservation. Different treatment options have been described, mostly in small clinical studies or experimental settings. These include nutritional support, neurohormonal blockade, reducing intestinal bacterial translocation, anemia and iron deficiency treatment, appetite stimulants, immunomodulatory agents, anabolic hormones, and physical exercise regimens. Currently, nonpharmacological therapy such as nutritional support and physical exercise are considered central to cachexia prevention and treatment.
Keywords: Anemia; Heart failure; Muscle wasting; Nutrition; Physical exercise; Prognosis